Antibacterial Analysis of Talinum triangulare Against Staphylococcus aureus and Escherichia coli - Kamelia Marlina; Wahyuningsih Nuriyah; Supriyadi; Zein Suharno (E3S Web of Conferences, 2024)
This study aims to determine whether Talinum triangulare can inhibit the growth of Staphylococcus aureus and Escherichia coli. The T. triangulare used in this research were the leaves, stems and roots. Simplicia leaves, stems and roots of T. triangulare were extracted by maceration using 96% ethanol solvent, then filtered and thickened using a rotary evaporator. Testing of T. triangulare against S. aureus and E. coli using the agar well diffusion method. The test solutions used were concentrations of 20%, 40%, 60%, 80%, 100% as well as positive and negative controls as comparisons. The positive control used amoxicillin while the negative used sterile distilled water. The results of the antibacterial activity test were shown by the formation of a growth inhibition zone (ZHP) for S. aureus and E. coli. Statistical tests using One way ANOVA followed by Post Hoc tests in the form of LSD. Research data shows that leaf extract is the most effective in inhibiting the growth of S. aureus and E. coli compared to roots and stems. The most effective concentration in inhibiting the growth of S. aureus and E. coli bacteria is 100%. The increase in concentration is directly proportional to the extent of the clear zone formed around the well. T. triangulare leaf, stem and root extracts were more effective in inhibiting S. aureus than E. coli.